Voluntary corporate liquidations - Kim, E.Han; Schatzberg, John D. (Journal of Financial Economics, 1987)
This paper examines possible motives for and consequences of voluntary corporate liquidations. Specifically, the procedural and tax differences between voluntary liquidations and other control-changing transaction devices are analyzed. An empirical investigation of successful liquidations shows that the announcement of liquidation reduces the risk of liquidating shares, that the shareholders receive substantial gains from successful liquidations, and that the average gains to the acquiring shareholders are not significantly different from zero. These findings suggest that the liquidating firms' assets have been underutilized before liquidation and that voluntary liquidations lead to higher-valued reallocations of corporate resources.